ANALYSIS OF THE BEARING CAPACITY OF PILE FOUNDATIONS IN THE DESIGN AND CONSTRUCTION PROJECT OF AN ACCESS BRIDGE ACROSS THE CISADANE RIVER IN THE PIK-2 EXTENTION AREA - Muhammad Rizki Aulia; Aliem Sudjatmiko (SEAN Institute, 2023)
A bridge is defined as a building construction structure that connects two tracks cut off due to rivers, lakes or other crossings. Bridges have an important role in facilitating the flow of vehicles. In construction definitely requires a foundation. The foundation is a construction that functions as a support above it. In general, bridges have two structural parts : the upper structure receiving direct loads and the lower structure carrying all the loads above it. The upper structure consists of a curb, vehicle floor plate (slab), main beam and diaphragm beam. While in the lower structure there are abutments and pillars, the construction of a bridge definitely requires analysis and calculation, the purpose of making a journal is to calculate the carrying capacity of pilecap foundations, piles, with soil carrying capacity using NSPT and get results on each calculation of the maximum load of piles with qualified soil that is greater than Qall da=with example P1 which is 47.279 tons/pole < Qall = 47.28 tons ( OK), P2 which is 47.274 tons/pole < Qall = 47.28 tons (OK), P3 which is 47.268 tons/pole < Qall = 47.28 tons (OK). From these calculations, it can be concluded that the pilecap with 45 piles with a diameter of 80 cm is able or safe to support the construction on it.